エンダービーランド チイキ ノ ベチェルナヤ サン オヨビ リーセル・ラルセン サン チイキ チガク チョウサ エンガン チガク チョウサ ホウコク 1988 (JARE-29) - 牧本, 博; マキモト, ヒロシ; 浅見, 正雄; アサミ, マサオ; 安仁屋, 政武; アニヤ, マサム; 林, 正久; ハヤシ, マサヒサ; Grew, Edwqrd S.; Makimoto, Hiroshi; Asami, Masao; Aniya, Masamu; et al. (1988)
P(論文) 第29次南極地域観測隊夏隊は, 1988年2月14日から22日の間, エンダービーランドのベチェルナヤ山地域及びリーセル・ラルセン山地域の地質・地形調査を行った。エンダービーランドを構成する二岩体に大別される古期変成岩類のうち, 前者はレイナー岩体, 後者はナピア岩体をそれぞれ代表する地域で, 地質調査では岩石学的研究, 年代学的研究のための試料採集を中心とした。地形調査では氷河地形, 周氷河地形の観察と氷河堆積物, 析出塩類等の採集を行った。これらの行動概要及び調査結果の概要を報告する。 The field party of the 29th Japanese Antarctic Research Expedition carried out geological and geomorphological field work in the Mt. Vechernyaya and Mt. Riiser-Larsen areas of Enderby Land from February 14th to 22nd, 1988. The main objective of geological survey was to obtain rock samples for petrological and geochronological studies on the Rayner and Napier Complexes which constitute Mt. Vechernyaya and Mt. Riiser-Larsen, respectively. Geomorphological field work comprised visual observations of glacial and periglacial landforms and sampling of efflorescences and glacial deposits. The present report gives detailes of the field operation and preliminary results of the field observations. departmental bulletin paper